Model of shariah governance for empowering Islamic non-governmental organisations in humanitarian mission - Nadhirah, Nordin; Siti Khatijah, Ismail; Sumayyah, Abdul Aziz (2020)
This study aims to propose a model of shariah governance for Islamic Non-Governmental Organizations. It will define the true concept of shariah governance from a holistic worldview, then to elucidate its theoretical framework for Islamic Non-Governmental Organizations. The issue of defining shariah governance has received a massive amount of attention since the turn of the 20th century. Initially, the governance principles have been practised by most organisations all around the world at all levels. However, there is a great diversity between the principles of governance applied in most Western-led institutions with the principles of shariah governance. This leads to the discussion on revisiting the concept of governance from a shariah perspective. The study utilises the grounded theory, which is a qualitative approach that generates theory from observation. In addition, data collection is also supported through a semi-structured interview method and focused group discussions. The data of this study were then analysed using thematic analysis. The study makes it clear what is a theoretical framework that constructs this model. This model has a flexible theoretical framework which is explained by essential components which are Iman, Islam and Ihsan, and based on the concept of khalifah. This paper emphasises that shariah compliance is the fundamental element of shariah organisation and thus, shariah governance is an ultimate approach to ensure such observance and hence increase the level of public trust in Islamic Non-Governmental Organisations.